2009
DOI: 10.1136/gut.2009.188946
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat area is an independent predictive biomarker of outcome after first-line bevacizumab-based treatment in metastatic colorectal cancer

Abstract: This study provides the first evidence that high VFA independently predicts a poorer outcome in patients given first-line bevacizumab-based treatment for MCC. However, this predictive biomarker needs to be validated in a different dataset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
149
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(166 citation statements)
references
References 55 publications
3
149
2
3
Order By: Relevance
“…However, the lack of effective prognostic prediction markers to stratify the patients remains a major challenge to establish an optimal personalized treatment paradigm of using these antiangiogenic agents to date. In a continuous effort to identify more effective prognostic markers, 'adiposity' has recently attracted research interest as a potential clinical biomarker to evaluate the efficacy of applying VEGF-targeted antiangiogenic therapy to treat a variety of cancers, including colon cancer (7,19), renal cell carcinoma (20,21) and ovarian cancer (9). However, previous studies generated somehow conflicting results (7,19,20,21).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, the lack of effective prognostic prediction markers to stratify the patients remains a major challenge to establish an optimal personalized treatment paradigm of using these antiangiogenic agents to date. In a continuous effort to identify more effective prognostic markers, 'adiposity' has recently attracted research interest as a potential clinical biomarker to evaluate the efficacy of applying VEGF-targeted antiangiogenic therapy to treat a variety of cancers, including colon cancer (7,19), renal cell carcinoma (20,21) and ovarian cancer (9). However, previous studies generated somehow conflicting results (7,19,20,21).…”
Section: Discussionmentioning
confidence: 79%
“…Maintenance bevacizumab (%) Percentage of SFA to whole body size f 3 Percentage of VFA to whole body size f 4 Mean CT number (pixel value) of SFA f 5 SD of the CT number of SFA f 6 Mean CT number (pixel value) of VFA f 7 SD of the CT number of VFA f 8 Size (volume) ratio between SFA and VFA BMI, body mass index; CT, computed tomography; ID, identity; SFA, subcutaneous fat area; VFA, visceral fat area; SD, standard deviation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies have shown contradictory results, postulating decreased efficacy of bevacizumab in obese patients [13,20,21]. In fact, response rates, time to progression as well as survival was worse in patients receiving bevacizumab with a higher BMI [21]. The authors speculate it might be higher circulating levels of VEGF conferring resistance to bevacizumab alongside higher volume of distribution in obese patients [13].…”
mentioning
confidence: 93%
“…This might explain slightly better outcomes in obese patients receiving bevacizumab in our cohort of patients evaluated. However, other studies have shown contradictory results, postulating decreased efficacy of bevacizumab in obese patients [13,20,21]. In fact, response rates, time to progression as well as survival was worse in patients receiving bevacizumab with a higher BMI [21].…”
mentioning
confidence: 97%